2014
DOI: 10.1016/j.apcatb.2014.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Palladium doped perovskite-based NO oxidation catalysts: The role of Pd and B-sites for NOx adsorption behavior via in-situ spectroscopy

Abstract: a b s t r a c tPerovskite-based materials (LaMnO 3 , Pd/LaMnO 3 , LaCoO 3 and Pd/LaCoO 3 ) were synthesized, characterized (via BET, XRD, Raman spectroscopy, XPS and TEM) and their NO x (x = 1,2) adsorption characteristics were investigated (via in-situ FTIR and TPD) as a function of the nature of the B-site cation (i.e. Mn vs Co), Pd/PdO incorporation and H 2 -pretreatment. NO x adsorption on of LaMnO 3 was found to be significantly higher than LaCoO 3 , in line with the higher SSA of LaMnO 3 . Incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 49 publications
6
47
0
2
Order By: Relevance
“…Say et al 20 used vibrational spectroscopy to observe features attributed to adsorbed nitrite and nitrate at 323K after saturating the surface with 5 Torr NO 2 for 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Say et al 20 used vibrational spectroscopy to observe features attributed to adsorbed nitrite and nitrate at 323K after saturating the surface with 5 Torr NO 2 for 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the Table 1 increased, when they were doped with Pd, the increase of the surface area was observed, which was very likely indication that a more uniform coating of Pd [17]. It was also found that b-zeolite and ZSM-5 exhibited larger mesopore volume, the mesopore volume of b-zeolite and ZSM-5 were 0.075 and 0.053 cm 3 /g, respectively.…”
Section: Characterization Of Catalystsmentioning
confidence: 52%
“…This result indicated that the Pd species were highly dispersed on the surface of the carrier. The main reason was likely the small particle size, low volume percentile, or lack of crystallographic order in such phase [17,20].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Dentre os catalisadores conhecidos, destacam-se os materiais a base de metais nobres, como o paládio [8]. Entretanto, devido ao seu custo elevado, materiais ativos e mais econômicos têm sido propostos como alternativa ao uso destes metais [9,10].…”
unclassified
“…Estudos indicam que catalisadores a base de óxidos mistos, como as perovskitas, apresentam-se ativos e termoestáveis quando aplicadas a combustão do metano [9,10].…”
unclassified